The potential of caproate (hexanoate) production using Clostridium kluyveri syntrophic cocultures with Clostridium acetobutylicum or Clostridium saccharolyticum - Otten, Jonathan K.; Zou, Yin; Papoutsakis, Eleftherios T. (Frontiers in Bioengineering and Biotechnology, 2022)
Caproate (hexanoate) and other medium-chain fatty acids are valuable platform chemicals currently produced by petroleum or plant-oil based processes. Clostridium kluyveri, growing on short chain alcohols (notably ethanol) and carboxylic acids (such as acetate) is noted for its ability to perform chain elongation to produce 4- to 8-carbon carboxylates. C. kluyveri has been studied in monoculture and coculture conditions leading to relatively modest carboxylate titers after long fermentation times. To assess the biosynthetic potential of C. kluyveri for caproate production from sugars through coculture fermentations, in the absence of monoculture data in the literature suitable for our coculture experiments, we first explored C. kluyveri monocultures. Some monocultures achieved caproate titers of 150 to over 200 mM in 40-50 hours with a production rate of 7.9 mM/hour. Based on that data, we then explored two novel, syntrophic-coculture partners for producing caproate from sugars: Clostridium acetobutylicum and Clostridium saccharolyticum. Neither species has been cocultured with C. kluyveri before, and both demonstrate promising results. Our experiments of C. kluyveri monocultures and C. kluyveri – C. saccharolyticum cocultures demonstrate exceptionally high caproate titers (145-200 mM), fast production rates (3.25 to 8.1 mM/hr) and short fermentation times (18-45 hr). These results represent the most caproate produced by a C. kluyveri coculture in the shortest known fermentation time. We also explored the possibility of heterologous cell fusion between the coculture pairs similar to the results seen previously in our group with C. acetobutylicum and Clostridium ljungdahlii. Fusion events were observed only in the C. acetobutylicum – C. kluyveri coculture pair, and we offer an explanation for the lack of fusion between C. saccharolyticum and C. kluyveri. This work supports the promise of coculture biotechnology for sustainable production of caproate and other platform chemicals.